INVESTIGATION OF ANTIMICROBIAL ACTIVITY OF EUPHORBIA HIRTA LEAVES: Pharmaceutical Science-Pharmacognocy - GUPTA, REENA; GUPTA, JITENDRA (International Journal of Life Science and Pharma Research, 2019)
In India, folklore medicinal herbs have many traditional applications for the treatment of ailments of various bacterial and fungal infections. The authentication of such claim is essential which can be established by a scientific researcher. So, the aim of present research to investigate the antimicrobial activity of Euphorbia hirta leaves. The petroleum ether, methanolic and aqueous extracts of leaves of Euphorbia hirta belonging to family Euphorbiaceae were isolated for the antimicrobial activity by employing agar well diffusion method across a few selected organisms like B. subtilis, E. coli, S. aureus and S. cerevisiae. The phytochemical analysis of petroleum ether, methanolic and aqueous extracts revealed the presence of tannins, related polyphenols, terpenes, anthocyanins, alcohols, steroids like ß-sitosterol and ß-amyrin. The antimicrobial activities due to phytoconstituents were assured by the absence or presence of zones of inhibition and by calculating the MIC values. The results concluded that antimicrobial activity of all the extracts were revealed from moderate to significant in contrast to standard.